Discovery Learning with Scaffolding To Promote Mathematical Creative Thinking Ability And Self-Efficacy - Jatisunda, Mohamad Gilar; Suciawati, Vici; Nahdi, Dede Salim (Al-Jabar: Jurnal Pendidikan Matematika, 2020)
Mathematical creative thinking ability and self-efficacy are a combination of abilities students need to have when studying mathematics. Mathematical learning is expected to improve both abilities. However, teachers still use conventional learning such as direct teaching, which results in a low increase in students' mathematical creative thinking abilities and self-efficacy. So we need alternative student-centred learning and teachers as facilitators who provide scaffolding. The study was conducted to obtain a description of the discovery learning process with scaffolding which aims to improve the ability to think creatively and self-efficacy. Two quasi-experimental designs with three class groups were used: The Matching-only Pretest-posttest Control Group Design was used to measure mathematical creative thinking skills, and The Matching-only Posttest-only Control Group Design was used to measure the self-efficacy scale. Based on the results of one-way ANOVA, the mathematical creative thinking ability of students discovery learning with scaffolding is better than discovery learning and conventional learning. Likewise, this happens to 'self-efficacy, based on the one-way ANOVA that students' self-efficacy of discovery learning with scaffolding is better than discovery learning and conventional learning. The learning process of discovery learning with scaffolding has a positive impact on the improvement of mathematical creative thinking abilities and self-efficacy